2000
DOI: 10.1017/s0272263100002023
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Instruction and Learner-Internal Factors In The Acquisition of L2 Morphosyntax

Abstract: This study considers the role of instruction, second language (L2) input, first language (L1) transfer, and Universal Grammar (UG) in the development of L2 morphosyntactic knowledge. Specifically, it investigates the acquisition of the Spanish morpheme se by English-speaking adult learners. Participants included 91 university students and 30 Spanish native-speaker controls. Learners received form-focused, communicative instruction on se for one week and were tested before, immediately following, and 24 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 62 publications
3
50
2
Order By: Relevance
“…This hypothesis was formalised by Oshita (2001) as the 'Unaccusative Trap Hypothesis' (UTH), and it is based on the presupposition that learners initially treat the subject as the external argument in all intransitive structures, therefore treating unaccusatives as unergatives. L2 speakers are reported to be able to recover from this initial misanalysis and fully acquire the target grammar (Zobl 1989;Sorace 1995;Hertel and Pérez-Leroux 1999;Toth 2000;Hirakawa 2003;Lee 2004;Montrul 2005). The reverse overgeneralisation pattern (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was formalised by Oshita (2001) as the 'Unaccusative Trap Hypothesis' (UTH), and it is based on the presupposition that learners initially treat the subject as the external argument in all intransitive structures, therefore treating unaccusatives as unergatives. L2 speakers are reported to be able to recover from this initial misanalysis and fully acquire the target grammar (Zobl 1989;Sorace 1995;Hertel and Pérez-Leroux 1999;Toth 2000;Hirakawa 2003;Lee 2004;Montrul 2005). The reverse overgeneralisation pattern (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the empirical data and research regarding typologically different languages (e.g., Sulkala 1996) has made it increasingly clear that some supposedly nontransferable structures find their way into learners' production. Some resent research (e.g., Toth 2000;Montrul 2000;Miličevič 2000) has suggested, contradicting former opinions, that morphology is the module of grammar most affected by L1 transfer. The experimental studies, accomplished mainly in the theoretical framework of Markedness Differen-tial Hypothesis but also Full Transfer/Full Access-hypothesis (Novakovič 2004) are focused on free morphology and morphosyntax.…”
Section: First Language Influence In Morphologymentioning
confidence: 96%
“…Though the complete explanation of the Turkish clitic system is beyond the scope of this paper,* verbs such as aç-mak 'to open,' kapa-mak 'to close,' and kir-mak 'to break' function the same in terms of clitic markings for the causative/ decausative alternations as these verbs in Spanish, but as mentioned above, there is substantial difference depending on the lexical item. showed that LI English speakers are at an inherent disadvantage when it comes to clitic acquisition; however, Toth (2000) demonstrates how focused instruction improves learners' use of se. Similarly, 'White (1991) illustrates that without negative evidence, L2 Spanish speakers have difficulty using se because of its complexity in Spanish.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Although other divisions of the use of se have been proposed (e.g. Toth, 2000), these seven categories are the basis of analysis for this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation